2023
DOI: 10.1186/s12964-023-01053-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting and regulation of autophagy in hepatocellular carcinoma: revisiting the molecular interactions and mechanisms for new therapy approaches

Abstract: Autophagy is an evolutionarily conserved process that plays a role in regulating homeostasis under physiological conditions. However, dysregulation of autophagy is observed in the development of human diseases, especially cancer. Autophagy has reciprocal functions in cancer and may be responsible for either survival or death. Hepatocellular carcinoma (HCC) is one of the most lethal and common malignancies of the liver, and smoking, infection, and alcohol consumption can lead to its development. Genetic mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 259 publications
0
9
0
Order By: Relevance
“…Recently, accumulating studies have suggested that autophagy is involved in the development and progression of HCC 30–32 . In our study, we first identified the UBA52 gene, one of the most highly expressed autophagy‐related genes in HCC in the GEPIA database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, accumulating studies have suggested that autophagy is involved in the development and progression of HCC 30–32 . In our study, we first identified the UBA52 gene, one of the most highly expressed autophagy‐related genes in HCC in the GEPIA database.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, accumulating studies have suggested that autophagy is involved in the development and progression of HCC. 30 , 31 , 32 In our study, we first identified the UBA52 gene, one of the most highly expressed autophagy‐related genes in HCC in the GEPIA database. Then, we collected tissue samples from HCC patients and verified that the UBA52 expression was significantly increased in HCC samples.…”
Section: Discussionmentioning
confidence: 99%
“… 26 EMT is the mechanism most closely associated with tumor cell invasion and metastasis and is characterized by morphological and physiological changes, such as loss of cell polarity, disruption of intracellular junctions, and increased growth and invasion. 27 Multiple studies have shown that OVOL2, as a transcription factor, inhibits EMT in tumor cells. 22 , 28 , 29 This result is consistent with our research results.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed overview of the autophagy mechanisms involved in HCC development and progression have been recently published [ 264 , 265 ].…”
Section: Autophagymentioning
confidence: 99%